2018
DOI: 10.1111/jon.12553
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Atrophy in Multiple Sclerosis: A Systematic Review and Meta‐Analysis

Abstract: The SC is atrophied in MS. The magnitude of SCA is greater in progressive versus relapsing forms and correlates with clinical disability. The pooled estimate of annual rate of SCA is greater than reported rates of brain atrophy in MS. These results demonstrate that SCA is highly relevant as an imaging outcome in MS clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 102 publications
12
76
0
Order By: Relevance
“…39 However, we have a priori set our study duration at 1 year to obtain estimates for clinical trials and short-term observational studies; of note, we obtained annualized atrophy rates in line with pooled estimates from 94 studies (1.78%/year), 13 and the number of participants per arm was consistent with that obtained by other similar studies. Previous studies have shown that spinal cord atrophy predicts disease progression and conversion from CIS to RRMS over a long followup period.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…39 However, we have a priori set our study duration at 1 year to obtain estimates for clinical trials and short-term observational studies; of note, we obtained annualized atrophy rates in line with pooled estimates from 94 studies (1.78%/year), 13 and the number of participants per arm was consistent with that obtained by other similar studies. Previous studies have shown that spinal cord atrophy predicts disease progression and conversion from CIS to RRMS over a long followup period.…”
Section: Discussionsupporting
confidence: 75%
“…Sample size to detect 60% treatment effect on spinal cord atrophy over 1 year was lower for GBSI than CSA (CIS: 106 vs 830; RRMS: 95 vs 335; PMS: 44 vs 215; power = 80%; alpha = 5%). 5,12,13 It is crucial to obtain an accurate and precise longitudinal measurement of spinal cord atrophy, because it could be used to monitor disease progression and become a primary outcome measure in phase 2 clinical trials with neuroprotective therapies, not only in MS, but also in other neurodegenerative disorders. ANN NEUROL 2019;86:704-713 S pinal cord atrophy on magnetic resonance imaging (MRI) is a marker of neurodegeneration in multiple sclerosis (MS), 1,2 and is one of the main substrates of longterm disease progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…27 One large metadata study found, on average, that patients with multiple sclerosis lose 1.78%/year of their cervical SC area. 16 We do not need to assume that SC atrophy during 1 year in HP would be zero; however, a large study with .1200 asymptomatic participants spanning 20-80 years in age found that in both men and women the C2/C3 intervertebral level cross-sectional area had a minimum decrease of about 1% and a maximum decrease of roughly 4.5% spanning several decades. 32 Thus, we can be fairly certain that during the course of a 1-year follow-up, normal SC atrophy would, most likely, not surpass 1.5%.…”
Section: Discussionmentioning
confidence: 98%
“…Most studies of MR imaging-based SC atrophy comparisons of diseased with healthy SC measures have relied on interindividual variability calculated from crosssectional data. 16 Intraindividual variability in healthy participants (HP) is often ignored or assumed to be equivalent to the mean change (or SD) in SC atrophy measures. 9 The utility of using cerebral 3D MRIs, including the upper cervical cord (UCC), as a source of MUCCA calculations is based on the availability of this sequence in most patients.…”
Section: Discussionmentioning
confidence: 99%